Constraints Perceived by Rice Farmers in the Adoption of Rice Production Practices in Southern Province of Republic of Rwanda - Nzigiyimana Augustin, M. S. Nataraju, V. Govinda Gowda, (Indian Journal of Extension Education, 2022)
..